Synthesis and characterization of Biosilicate/F18 bioglass scaffolds for dental application - Abadia, Claudia Patricia Marin (Universidade Federal de São Carlos, 2019)
In this work, Biosilicate scaffolds were synthesized using the foam replica technique. Biosilicate is highly bioactive, biodegradable, antibacterial, and non-toxic. Despite of these properties, Biosilicate scaffolds present low mechanical strength, limiting their clinical applications. Therefore, our aim was to increase the mechanical properties of the Biosilicate scaffolds by several F18 glass coatings. First, the Ryshkewitch and Ashby & Gibson models were used to calculate the maximum theoretical compressive strength of the scaffolds in function of their porosity, taking into account the ideal conditions found in the literature. Biosilicate scaffolds were prepared through the foam replica technique; then, they were coated several times with F18 Bioglass slurry to eliminate their defects and reinforce their structures. The scaffolds were characterized by microstructure, total porosity, average cell size, and compressive strength. The material exhibited a total porosity of 82%, an average cell size of 525 μm, and compressive strength of 3.3 (± 0.3) MPa, values in the range of commercial scaffolds based on Hydroxiapatite and β-TCP. Scanning Electron Microscopy showed that F18 bioglass helped to remove surface defects and partially infiltrated the hollow Biosilicate-struts, increasing significantly the resistance of the material. Also, in vitro osteogenic differentiation of human Adipose-derived mesenchymal Stem Cells (hASCs) was evaluated using F18 glass-coated Biosilicate scaffolds and their ionic dissolution products. Gene expression profiles of cells were evaluated using the RT2 Profiler PCR microarray on day 21. Mineralizing tissue-associated proteins and osteogenic differentiation factor expressions were measured using Q-PCR. Additionally, alkaline phosphatase enzyme production and extracellular matrix mineralization were evaluated. The alkaline phosphatase activity, mineralization and bone-related gene expression of hASCs were significantly enhanced upon stimulation with both scaffolds and their ionic extracts. This work evidenced that F18 glass-coated Biosilicate scaffolds have a high potential for dental applications.
Síntese e caracterização de andaimes de Biosilicate/F18 biovidro para aplicação odontológica
Keywords: Biosilicato; Biovidro F18; Recobrimento; Diferenciação osteogênica; Biosilicate; F18 glass; Scaffold; Coating; Osteogenic Differentiation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA